Kawalan Perundangan Terhadap Pemakanan Halal Di Malaysia - Setiyawan Gunardi; Mohd Mahyeddin Mohd Salleh; Mustafa 'Afifi Bin Ab. Halim; Muneer Ali Abdul Rab; Mohd Soberi Awang (USIM Press, 2024)
Indexed by Scopus